Proposed Customer Knowledge Management (CKM) in the Truku Logistics Application Feature PT Biru Samudera Selatan - Satriawan, Nofri (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
Logistics processes that only make one trip in the transportation of goods result in inefficient logistics costs. Truku is an integrated digital logistics solution that provides added value to the company. the current condition of the truck application is still unable to optimally support services to users, especially the automatic payment transaction feature. The method used in this study is a conceptual model of Customer Knowledge Management (CKM) based on the Customer Relationship Management (CRM) phase and the Knowledge Management (KM) process. The results of the comparison of the features that have been formulated with the features available in the Truku application then become a reference for determining the proposed features that are recommended to PT Biru Samudera Selatan to be implemented in the Truku logistics application. So that later it can facilitate the development of application features based on the needs of the users of the Truku logistics application.